The diversities of Europe: From European modernity to the making of the European Union. (August 2014) - Kraus, Peter A.; Sciortino, Giuseppe
Looking for a concept that condenses the normative added value that the European Union may claim to embody vis-à-vis its member states, diversity would appear to be a first-rate candidate. For more than four decades, European institutions have endorsed a complex discourse about diversity that sharply differentiates the European project from the historical experiences of its member-states. The paper stresses the discontinuity inherent in the European Union project and the ways in which diversity is used in European Union discussions. It highlights the existence of several, and only partly overlapping, notions of diversity embedded in the European project: as an acknowledgement of the historical and cultural diversity of member states; as protection of individual and group diversity within a putatively shared and egalitarian European public sphere; as an instrument for achieving political stabilization, market competitiveness, territorial cohesion and economic growth. As an introduction to the special issue on the diversities of Europe, the paper provides the general conceptual framework for the analyses of the four types of diversities analysed: language, religion, foreignness and gender.